2021
DOI: 10.1007/s10803-021-05055-z
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind and Moral Decision-Making in the Context of Autism Spectrum Disorder

Abstract: All rights reserved. No reuse allowed without permission. perpetuity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…In contrast, some research found reduced prosocial behavior in ASD. Ringshaw and colleagues (Ringshaw et al, 2022) found that boys with ASD between 6 and 12 years of age were less prosocial in a moral decision‐making task than matched neurotypical boys. Moreover, Lin and colleagues (Lin et al, 2012) found high‐functioning ASD adults to donate significantly less to non‐autism‐related social charities than neurotypical adults.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some research found reduced prosocial behavior in ASD. Ringshaw and colleagues (Ringshaw et al, 2022) found that boys with ASD between 6 and 12 years of age were less prosocial in a moral decision‐making task than matched neurotypical boys. Moreover, Lin and colleagues (Lin et al, 2012) found high‐functioning ASD adults to donate significantly less to non‐autism‐related social charities than neurotypical adults.…”
Section: Discussionmentioning
confidence: 99%
“…In this task, participants were required to respond to verbal instructions of increasing length and grammatical complexity by pointing to certain stimuli. Importantly, the NEPSY-II has been translated into several languages and used with success in resource-limited countries including South Africa (Mulenga et al 2010;Ringshaw et al 2022).…”
Section: Language Comprehensionmentioning
confidence: 99%